Fabrication of a porous polyacrylonitrile nanofiber adsorbent for removing radioactive 60Co. (September 2022) - Pak, Geun Tae; Jo, Seonyoung; Kim, Tae Hyun; Lee, Keun-Woo; Huh, Tae-Hwan; Kwark, Young-Je; Yang, Hee-Man; Lee, Taek Seung
Abstract: A Co 2+ adsorbent was prepared using electrospun porous polyacrylonitrile (PAN) nanofibers, featuring easy recovery for reuse compared with a nanoparticle-based adsorbent. As an efficient ligand for Co 2+, ethylenediaminetetraacetic acid (EDTA) was introduced on the surface of porous PAN nanofibers with the aid of a branched polyethyleneimine (PEI) linker to obtain an adsorbent with carboxylic acid groups. On the adsorbent surface, the carboxylic acid and amine groups from EDTA could adsorb Co 2+ via ion exchange and chelation, and amine groups from PEI that remained after EDTA functionalization played a role in coordinating Co 2+ . The amine and carboxylic acid groups were simultaneously involved in the adsorption on the surface, making it possible to remove Co 2+ over a wide pH range. An investigation of the adsorption isotherms and kinetics of the nanofibrous adsorbent indicated that monolayer chemisorption was achieved with a maximum Co 2+ adsorption capacity of 8.32 mg/g. In addition, radioactive 60 Co was efficiently removed by the adsorbent with a removal extent of more than 98%. Considering the easy separation from Co 2+ solution and regeneration of the nanofibrous adsorbent and its availability in a wide pH range, the adsorbent has great advantages in practical applications. Graphical abstract: Image 1 Highlights: Electrospun porous PAN nanofibers were prepared to use as a radioactive 60 Co adsorbent. In a practical manner, the adsorbent can be used in a various type liquid waste with wide pH range. The adsorbent was efficiently regenerated to show excellent reusability.